MANAJEMEN LIFE SKILL PADA SEKOLAH UNGGUL MELALUI TEORI FISHBONE (Study Kasus Di SMA 1 Besuki) - Faifatur R., M. Kurma Nur (Jurnal Manajemen Pendidikan Islam Darussalam, 2022)
Students' skills are the capacity needed so students to carry out some tasks which are the development of the training results and experience gained. With the students' skills, students are able to operate a job easily and carefully. The existence of life skills learning is needed by students as an ability in themselves, besides it is expected that students are able to face problems and can find solutions. This learning is more precise if it jumps in directly, so students know how it is real. The reality in the field, of learning life skills in schools can be sufficient attention, the reason is that schools want to print their students into potential students in various fields both in the scientific field and the skill field. Learning experiences gained by students will inspire them when facing problems in real life. In developing learning experiences as far as possible the learning experiences provided are not only developing cognitive, affective, and psychomotor abilities but also life skills that are very necessary for the lives of future students as members of the community. The purpose of this research is to improve academic skills through contextual learning by using life skill-based learning models so that students are moreinterestedinparticipatinginlearning.